2006
DOI: 10.1002/mrd.20457
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the ovine interferon‐tau gene by a blastocyst‐specific transcription factor, Cdx2

Abstract: Expression of ovine interferon-tau (oIFNtau), a factor essential for the process of maternal recognition of pregnancy in ruminant ungulates, is restricted to the trophoblast. However, the molecular mechanisms by which oIFNtau expression is restricted to the trophectoderm have not been fully elucidated. The objective of this study was to determine whether oIFNtau gene transcription could be regulated through Cdx2 expression, a transcription factor implicated in the control of cell differentiation in the trophec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
76
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 43 publications
(80 citation statements)
references
References 44 publications
4
76
0
Order By: Relevance
“…Therefore, Cdx2 expression is thought to be associated with the initiation of TE fate. In ovine embryos, Cdx2 was localized to TE, but staining intensity appeared to decrease after implantation (45). Human trophoblasts derived from EBs showed increased expression of CDX2 (13).…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, Cdx2 expression is thought to be associated with the initiation of TE fate. In ovine embryos, Cdx2 was localized to TE, but staining intensity appeared to decrease after implantation (45). Human trophoblasts derived from EBs showed increased expression of CDX2 (13).…”
Section: Discussionmentioning
confidence: 97%
“…One of the most highly expressed genes during the gastrulation is TKDP4 and it may be key factor in early trophoblast proliferation (MacLean et al silences trophoblast IFNT transcription in concert with ETS-2 and CDX2 in TMCs, suggesting that these genes are also involved in regulating trophoblast cell proliferation and IFNT expression (Ezashi et al 2001, Imakawa et al 2006. On the other hand, the AP-2 family and Sp-1 may participate in the regulation of TGC-specific gene expression, even though the details of this regulation pathway remain to be studied (Limesand & Anthony 2001, Spencer et al 2004).…”
Section: Roles Of Trophoblast-specific Genes From Gastrulation To Permentioning
confidence: 99%
“…3). The numerous transcription factors found thus far as regulators of IFNT genes include ETS2 [30,31], activating protein 1 (AP-1; official symbol JUN) [32], CDX2 [24,27], homeobox protein distal-less 3 (DLX3) [33], and co-activators cAMP-response element binding protein (CREB)-binding protein (CREBBP) [34] and p300 [35]. Recently, we found that GATA2 and GATA3 could also increase IFNT transcription in our transient transfection system [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…The Renilla luciferase-pRL-TK vector (Promega), driven by the herpes simplex virus-thymidine kinase (HSV-TK) promoter, was used to normalize the transfection efficiency [27]. Amount of reporter construct used relative to that of the internal control vector pRL-TK was 20:1.…”
Section: Plasmid Transient Transfection and Luciferase Assaymentioning
confidence: 99%
See 1 more Smart Citation